Beyond tumor mutation burden: tumor neoantigen burden as a superior prognostic biomarker in resected gastric cancer - Lu, Tingting; Cao, Jingyi; Liu, Peng; Pan, Xiaoxin; Shen, Yiming; Wang, Jian; Chen, Zhida; Liu, Yi; Zhang, Fenglin; Zhang, Haiya; Zhang, Gan; Wang, Yi; et al. (Frontiers in Immunology, 2026)
IntroductionGastric cancer is one of the most diagnosed cancers and a major contributor to cancer-related death in China. Recent studies have demonstrated the failure of tumor mutational burden (TMB) in predictive accuracy. Here, we aimed to evaluate the prognostic value of tumor neoantigen burden (TNB) to predict the clinical outcome among patients undergoing gastric cancer resection.MethodsThis study performs whole exome and transcriptome sequencing of tumor tissues of 85 gastric cancer patients who underwent resection surgery. The prognostic value of TMB and TNB in Chinese gastric cancer patients were evaluated, respectively.ResultsIn contrast to TMB, TNB achieved significance in predicting overall survival at both early (a median follow-up period of 23.5 month) and late (a median follow-up period of 35.5 month) timepoints (p-value<0.05), particularly with expanding 2-year and 3-year restricted mean survival time (RMST). According to the comparative enrichment and protein-protein interaction analysis of TNB- and TMB-associated genes, we found the upregulated TNB-associated genes were significantly enriched in hormone and nutrient sensing cascades, whereas their counterparts were predominantly linked to cytoskeletal development. In addition, we also noticed an increased infiltration of neutrophils in TNB-High group (p-value=0.04).DiscussionIn summary, this study indicated that the prognosis of TNB-High patients was significantly better than their counterparts, which might be associated with impaired energy metabolism.